PENGARUH RETURN ON ASSET DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PT BANK CENTRAL ASIA TBK - Dessy Safitri; Achmad Ludvy (Journal of Research and Publication Innovation, 2024)
This study aims to examine the impact of Return On Asset and Earning Per Share on the stock price of PT Bank Central Asia Tbk from 2013 to 2022. The research employs a quantitative descriptive method. The findings reveal that Return On Asset has a negative and significant partial effect on the stock price of PT Bank Central Asia Tbk, as indicated by t-value of -1.739 < t-table 2.365, accepting H0 and rejecting Ha, with a significance level of 0.126 > 0.05. Earning Per Share shows a positive and significant partial effect on the stock price of PT Bank Central Asia Tbk, with t-value of 8.093 > t-table 2.365, accepting H0 and rejecting Ha, with a significance level of 0.000 > 0.05. Simultaneously, Return On Asset and Earning Per Share have a significant impact on the stock price of PT Bank Central Asia Tbk, with F-value of 32.798 < F-table 19.4 and a significance level of 0.000 < 0.05, contributing 90.4% to the model.